Legal Protection for Health Workers under Building Facility Standards - Anailyka, Putrinda Wisty; Srigantiny, Fivit; Lany, Arman (Research Horizon, 2025)
Inadequate building facilities at Puskesmas, as mandated by Permenkes Number 19 of 2024, pose risks to health workers and patients, potentially leading to medical disputes and compromised service quality. This study analyzes the implementation of Puskesmas building facility standards and evaluates the legal protection framework for health workers under Law Number 17 of 2023 and Permenkes No. 19 of 2024. Normative legal research was conducted through document and literature studies, analyzing primary, secondary, and tertiary legal materials. Many Puskesmas fail to meet building standards, with issues like limited-service space, poor room layouts, and inadequate safety facilities, increasing risks for health workers. Legal protections exist but are hindered by implementation gaps, lack of legal education, and insufficient government support and help workers. Strengthening many regulatory enforcement, enhancing legal education, and improving facility compliance are critical to ensuring effective legal and many protections for health workers and quality health services.